An N6-Methyladenosine-Related Gene Set Variation Score as a Prognostic Tool for Lung Adenocarcinoma - Zhang, Huijuan; Hu, Jing; Liu, Aina; Qu, Huajun; Jiang, Fenge; Wang, Congcong; Mo, Steven; Sun, Ping (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is the most prevalent type of RNA modifications. We hypothesized that the expression patterns of m6A-related genes may be able to score the individual's m6A potential in lung adenocarcinoma (LUAD). An m6A-related gene set variation score (m6A-GSVS) for each individual was generated using the RNA sequencing data of LUAD in The Cancer Genome Atlas with GSVA methods. Subsequently, we investigated the association between the m6A-GSVS and stemness, tumor mutational burden, the expression of three immune checkpoints, tumor-infiltrating lymphocytes, and prognosis. We found the m6A-GSVS elevated in LUAD compared with healthy lung tissue and showed high correlation with stemness and TMB, low correlation with the expression of CD274 and CTLA4. The activated CD4 T cells were more in the LUAD samples with higher m6A-GSVS. Multiple biological processes and pathways vary in LUAD samples with different m6A-GSVSs, such as “Cell cycle”, “DNA replication”, and “RNA degradation” were significantly enriched in high m6A-GSVS samples. Furthermore, the m6A-GSVS was an independent prognostic indicator in LUAD. In conclusion, we proposed an m6A-GSVS in LUAD. It is a putative indicator for evaluating the ability to RNA m6A, an independent prognostic indicator, associated with tumor stemness and may be associated with the efficacy of anti-immune checkpoint treatment in LUAD.